Rhinomaxillary Mucormycosis with Palatal Perforation: A Case Report - Sreenath G; A. Ravi Prakash; M. Rajni Kanth; P. Sreenivas Reddy; Pavani Vidhyadhari (Journal of Clinical and Diagnostic Research, 2014)
Mucormycosis are a group of invasive infections caused by filamentous fungi of the Mucoraceae family. Mucormycosis is essentially limited to immunocompromised patients with poorly controlled diabetes mellitus, hematologic malignancy, organ transplant, chemotherapy, chronic renal insufficiency, malnutrition, deferoxamine therapy and severe burns. The fungi invade arteries leading to thrombosis that subsequently causes necrosis of hard and soft tissues. Here, we present a case report of a 50-year-old diabetic patient with rhinomaxillary form of mucormycosis.